The scaffolding. Collective individuation and the word worker: the Renault case - Scheller, Livia (Rivista Italiana di Filosofia del Linguaggio, 2023)
In this text the use of the word “scaffolding” is attributed to the action taken inside Renault, a French car factory.  Such action must allow us to address a conflict of criteria on the quality of work between company managers, internal unions and line workers.  The framework for defining and processing this conflict is proposed by a collective of “activity clinicians”, a sector of French work psychology whose research starts from situations of conflict in work activity that need to be transformed. The scaffolding that the clinicians propose will allow the development of the worker voice through the creation of a new function, that of the “worker referent”. Such scaffolding will have to find ways to structurally implant the new function, to develop its decision- making power in the exchange with the functions of managing and structuring the entire company. Only time will tell whether the innovative function will make obsolete the subordination contract that every employee and in a radical way the worker function, is obliged to undergo. A lot will depend on the dialogical balance of power between the managerial and operational functions.